Depression, Anxiety, and Stress Symptoms in Patients With Beta Thalassemia Major in Almadinah Almunawwarah, Saudi Arabia - Zolaly, Mohammed A (Cureus, 2020)
Introduction Beta thalassemia major (BTM) is a chronic hereditary blood disorder. Patients are dependent on blood transfusion and are prone to multiple comorbidities. Depression, anxiety, and stress (DAS) can complicate their condition. No reports from Saudi Arabia to measure DAS in BTM patients. We report the prevalence of DAS symptoms in our BTM patients using the DASS-21 (Depression, Anxiety, and Stress Scale - 21 Items) test. Methods A cross-sectional study including adolescents and adults aged 14 years and above with BTM treated in Almadinah Almunawwarah and excluding patients who had bone marrow transplant or with central nervous system insults were performed. Results A total of 31 male and 31 female patients were enrolled, with a mean age of 24.32 ± 7.05 years. Depression symptoms were detected in 60 % of patients, anxiety symptoms were detected in half of the studied group, and stress symptoms were detected in 38.7% of patients. We found a significant positive correlation between DAS and DASS total score. Age below or above 18, parent’s employment, patient’s educational level, and status of satisfaction about medical care were statistically significant in having positive effects on scores of DAS symptoms.  Conclusions BTM patients are prone to develop psychological disorders, which can affect the course of the disease. Our results are comparable to international and Arab population studies, which have the highest reported prevalence. It is important to not ignore the psychological evaluation of patients with BTM and to refer them for proper evaluation and management.